IUTAM Symposium on Recent Advances in Moving Boundary Problems in Mechanics : proceedings of the IUTAM Symposium on Moving Boundary Problems, Christchurch, New Zealand, February 12-15, 2018 /: proceedings of the IUTAM Symposium on Moving Boundary Problems, Christchurch, New Zealand, February 12-15, 2018. ([2019]) - Unknown
No abstract available